The formation of Chinese humanist ethics a hermeneutic-semiotic perspective - Youzheng, Li (Enrich Professional Publishing (S) Private Limited Silkroad Press, 2013)
This book makes Chinese ethics theoretically more understandable through an interdisciplinary approach, from the perspectives of hermeneutics and semiotics. The Analects of Confucius are structurally analyzed so as to reveal the epistemological preconditions and pragmatic rationality implied in the maxims of this important classic. The composition, constitution, and structure of the Han Academic system are studied; other pre-Qin Chinese ideologies, like Taoist nihilism and Mencian-Confucian ethics are also discussed